Forehand And Backhand Ability Of Table Tennis Athletes: How Much Is The Effect With Multiball Training? - Al Farrel, M. Aufa Rifki; Setiawan, Moch Iman; Nugroho, Wahyu Adhi; Maulana, Muhammad Andi (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. The purpose of this study is to determine 1) The effect of multiball training on forehand shots. 2) The effect of multiball training results on backhand shots. 3) Comparison of the results of forehand and backhand shot techniques using the multiball training method on the training results of table tennis union athletes sekar kemuning permai Cirebon City. The problem in this study was to determine the effect of table tennis multiball training on the ability of forehand and backhand shots at PTM SKP Athletes in Cirebon City. Materials and methods. This study used an experimental method with a 'pretest - posttest group design' design. The population in this study were 16 athletes of PTM SKP Cirebon City. Sampling of this study was done by purposive sampling. The instrument used multiball training on the accuracy of forehand and backhand shots. Data analysis using t test significance level 52.08% (Forehand) and 53.01% (Backhand). Results. The results showed that (1) There is an effect of multiball training on forehand shots with t count 4.710 and t table 2.365 and significance 0.002 <0.05. (2) There is an effect of multiball training on backhand shots with tcount 3,550 and ttable 2,365 and a significance value of 0.009 <0.05. (3) There is an increase in accuracy of forehand and backhand shots, with a percentage of forehand results of 52.08% and backhand 53.01%. Conclusions. From these results it can be concluded that there is a significant effect of multiball training on the accuracy of forehand and backhand.